Oxidative stress and epigenetic modifications in the pathogenesis of diabetic retinopathy. (September 2015) - Kowluru, Renu A.; Kowluru, Anjan; Mishra, Manish; Kumar, Binit
Abstract: Diabetic retinopathy remains the major cause of blindness among working age adults. Although a number of metabolic abnormalities have been associated with its development, due to complex nature of this multi-factorial disease, a link between any specific abnormality and diabetic retinopathy remains largely speculative. Diabetes increases oxidative stress in the retina and its capillary cells, and overwhelming evidence suggests a bidirectional relationship between oxidative stress and other major metabolic abnormalities implicated in the development of diabetic retinopathy. Due to increased production of cytosolic reactive oxygen species, mitochondrial membranes are damaged and their membrane potentials are impaired, and complex III of the electron transport system is compromised. Suboptimal enzymatic and nonenzymatic antioxidant defense system further aids in the accumulation of free radicals. As the duration of the disease progresses, mitochondrial DNA (mtDNA) is damaged and the DNA repair system is compromised, and due to impaired transcription of mtDNA-encoded proteins, the integrity of the electron transport system is encumbered. Due to decreased mtDNA biogenesis and impaired transcription, superoxide accumulation is further increased, and the vicious cycle of free radicals continues to self-propagate. Diabetic milieu also alters enzymes responsible for DNA and histone modifications, and various genes important for mitochondrial homeostasis, including mitochondrial biosynthesis, damage and antioxidant defense, undergo epigenetic modifications. Although antioxidant administration in animal models has yielded encouraging results in preventing diabetic retinopathy, controlled longitudinal human studies remain to be conducted. Furthermore, the role of epigenetic in mitochondrial homeostasis suggests that regulation of such modifications also has potential to inhibit/retard the development of diabetic retinopathy. Highlights: Diabetes induces oxidative stress, and increased cytosolic reactive oxygen species damage retinal mitochondrial function and DNA. Enzymes responsible for epigenetic modification are altered, and genes important in mitochondrial homeostasis are epigenetically modified. The superoxide scavenging system and mtDNA-transcription are compromised, further fueling into the vicious cycle of free radicals. Regulation of mitochondrial homeostasis has potential to offer therapeutic modalities for the treatment of diabetic retinopathy.